PERANCANGAN SISTEM BASIS DATA ONLINE MONITORING KUALITAS AIR DI SUNGAI CILIWUNG - Yudo, Satmoko (Jurnal Air Indonesia, 2016)
Population growth in the Jakarta city that continues to rise each year, this has resulted in environmental pollution, especially pollution of the Ciliwung river continues to grow. Nowadays various attempts have been made in terms of prevention of pollution of the river Ciliwung. One of the efforts to control pollution in the river Ciliwung is monitoring the quality of water in rivers and creeks Ciliwung. This monitoring is done in real-time and online, where the water quality data sent to data centers and analyzed into information that can be displayed at any time and anywhere through the Internet. If there are pollutants that enter the river so heavilly polluted in certain time, the government or the authorities that manages the river can take action to control pollution. To support online monitoring system running well required database management system (DBMS) for storing water quality data at any time and integrated well. Keywords : river pollution, water quality monitoring online, Ciliwung river, design database.